ENDOSCOPIC THIRD VENTRICULOSTOMY IN THE TREATMENT OF NORMOTENSIVE HYDROCEPHALUS. A CLINICAL CASE - Orest I. Palamar; Andriy P. Huk; Bohdan O. Davydenko; Oleksandr I. Troian; Kateryna M. Molotkovets (Клінічна та профілактична медицина)
Introduction. Normotensive hydrocephalus is an abnormal accumulation of cerebrospinal fluid in the ventricles of the brain. This causes an increase in the enlargement of the ventricles and an increase in intracranial pressure. Finally, this will cause gait impairment, decreased cognitive function, and urinary incontinence. Normal pressure hydrocephalus is a potentially clinically reversible disease. For this purpose, ventriculoperitoneal shunt is used. However, ventriculoperitoneal shunting has a high rate of complications. An alternative to ventriculoperitoneal shunting is endoscopic third ventriculostomy.